Multi-timescale capacity configuration optimization of energy storage equipment in power plant-carbon capture system. (5th June 2023) - Chen, Xianhao; Qiu, Ruohan; Wu, Xiao
Graphical abstract: Highlights: Multi-timescale energy storage capacity configuration approach is proposed. Plant-wide control systems of power plant-carbon capture-energy storage are built. Steady-state and closed-loop dynamic models are jointly used in the optimization. Economic, emission, peak shaving and load ramping performance are evaluated. The performance of various energy storages is compared under changing conditions. Abstract: Deploying energy storage technologies into power plant-carbon capture systems has received much attention since it can greatly improve the flexibility of the plant, thus enhancing the competitiveness in the electricity market. Determining the reasonable capacity of the energy storage equipment is the key to ensuring a reliable, economic, flexible and low carbon operation of the entire plant. To this end, this paper proposes a multi-timescale capacity configuration optimization approach for the deployment of energy storage equipment in the power plant-carbon capture system, in which both the long-timescale economic, emission, peak loading shifting performance, and the short-timescale load ramping performance are evaluated through the joint use of the steady-state and closed-loop dynamic plant models. Case study on the capacity configuration of the molten-salt heat storage equipment in the power plant-carbon capture system shows that the proposed multi-timescale capacity configuration optimization approach can reduce the totalized costs by 2.15% compared with the conventional capacity configuration approach. Other energy storage technologies such as battery and lean/rich solvent storage are also optimized and compared under different electric market conditions to provide broader insights on their roles in the power plant-carbon capture system.